PATTERNS OF CARE FOR LUNG CANCER IN RADIATION ONCOLOGY DEPARTMENTS OF TURKEY - (:unkn) unknown (ELSEVIER SCIENCE INC, 2008)
Purpose: To determine the patterns of care for lung cancer in Turkish radiation oncology centers. Methods and Materials: Questionnaire forms from 21 of 24 (87.5%) centers that responded were evaluated. Results: The most frequent histology was non-small cell lung cancer (NSCLC) (81%). The most common postoperative radiotherapy (RT) indications were close/(+) surgical margins (95%) and presence of pN2 disease (91%). The most common indications for postoperative chemotherapy (CHT) were >= IB disease (19%) and the presence of pN2 disease (19%). In Stage IIIA potentially resectable NSCLC, the most frequent treatment approach was neoadjuvant concomitant chemoradiotherapy (CHRT) (57%). In Stage IIIA unresectable and Stage IIIB disease, the most frequent approach was definitive concomitant CHRT (91%). In limited SCLC, the most common treatment approach was concomitant CHRT with cisplatin+etoposide for cycles 1-3, completion of CHT to cycles 4-6, and finally prophylactic cranial irradiation in patients with complete response (71%). Six cycles of cisplatin + etoposide CHT and palliative thoracic RT, when required, was the most commonly used treatment (81%) in extensive SCLC. Sixty-two percent of centers did not have endobronchial brachytherapy (EBB) facilities. Conclusion: There is great variation in diagnostic testing, treatment strategies, indications for postoperative RT and CHT, RT features, and EBB availability for LC cases. To establish standards, national guidelines should be prepared using a multidisciplinary approach. (c) 2008 Elsevier Inc.
Keywords: Patterns of care; Lung cancer; Radiation oncology; Radiotherapy; Chemotherapy; THORACIC RADIOTHERAPY; POSTOPERATIVE RADIOTHERAPY; RANDOMIZED-TRIAL; CONCURRENT CHEMOTHERAPY; SURVEY PCS; PHASE-III; CARCINOMA; THERAPY; BRACHYTHERAPY; CISPLATIN